Analisis Kinerja Keuangan dengan Menggunakan Metode Rasio Keuangan pada Perusahaan Food and Baverage yang Terdaftar Dibursa Efek Indonesia Tahun 2019 – 2023 - Mia Wulansari; Rosento Rosento (Universitas 45 Surabaya, 2024)
This research aims to analyze the financial performance of food and beverage sector companies listed on the Indonesia Stock Exchange (BEI) during the 2019-2023 period. This sector's financial performance has experienced fluctuations, especially due to the COVID-19 pandemic which has affected supply chains and consumption patterns. However, in 2023, the sector will begin to recover with a focus on product innovation, sustainability and improving operational efficiency to face global economic challenges. The data used is secondary data in the form of company financial reports, with an analysis method using financial ratios. Liquidity Ratios (Current Ratio, Quick Ratio, and Cash Ratio) assess the company's ability to meet short-term obligations. Solvency Ratios (Debt to Equity Ratio and Debt to Asset Ratio) measure a company's ability to fulfill long-term obligations. Profitability Ratios (Return on Investment and Return on Equity) are used to assess a company's ability to generate profits. The analysis results show that PT. Mayora Indah Tbk has satisfactory liquidity performance, but its solvency is above industry standards. PT. Indofood Sukses Makmur Tbk is stable in liquidity ratios but requires improvement in solvency. PT. Garudafood Putra Putri Jaya Tbk shows the need to improve its liquidity and profitability ratios during the 2019-2023 period.